2014
DOI: 10.1002/ca.22415
|View full text |Cite
|
Sign up to set email alerts
|

Arterial supply of the upper cranial nerves: A comprehensive review

Abstract: The arterial supply to the upper cranial nerves is derived from a complex network of branches derived from the anterior and posterior cerebral circulations. We performed a comprehensive literature review of the arterial supply of the upper cranial nerves with an emphasis on clinical considerations. Arteries coursing in close proximity to the cranial nerves regularly give rise to small vessels that supply the nerve. Knowledge of the arteries supplying the cranial nerves is of particular importance during surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…In the presented cohort, 7/9 patients underwent a frontolateral approach via a supraorbital or pterional approach. Olfactory nerve damage during frontolateral craniotomy include avulsion from the cribriform plate owing to frontal lobe retraction, injury to the tract during dissection causing axonal damage or disruption of arterial supply causing ischemia (Cardali et al, ; Hendrix et al, ). Surgical complications predispose patients to neurological deterioration (Buhl et al, ; Sanai et al, ; Grossman et al, ; Bartek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the presented cohort, 7/9 patients underwent a frontolateral approach via a supraorbital or pterional approach. Olfactory nerve damage during frontolateral craniotomy include avulsion from the cribriform plate owing to frontal lobe retraction, injury to the tract during dissection causing axonal damage or disruption of arterial supply causing ischemia (Cardali et al, ; Hendrix et al, ). Surgical complications predispose patients to neurological deterioration (Buhl et al, ; Sanai et al, ; Grossman et al, ; Bartek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…, B3). Thus, ACA, ACOM, and OA aneurysm locations display an anatomic risk factor potentially hampering olfactory function due to thromboembolic ischemic events or neurovascular compression (Hendrix et al, ). Kelkar et al () reported a case of bilateral ophthalmic aneurysms causing hyposmia which moderately improved after bilateral flow diversion and consequent aneurysm occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate understanding of the angioarchitecture of a dAVF is paramount when selecting the best treatment approach. Transvenous embolization is still preferred when dAVF has supply from arteries which supply cranial nerves, predominantly the internal carotid artery, and potentially extracranial to intracranial anastomosis (Natarajan et al, ; Hendrix et al, a,b). Transvenous embolization, however, may not be feasible when the venous system is stenosed or occluded (Hu et al, ).…”
Section: Discussionmentioning
confidence: 99%